Re-Visits the Grand Theory of Geoffrey Leech: Seven Types of Meaning - Sandra Yunira; Siska Fradina; Mathilda Sumbayak; Nunung Susilo Putri; Tatum Derin (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
Meaning is the field of the study discussed in semantic science. Semantics is a branch of linguistics that studies the meaning of words in languages. In contrast, linguistics is the study of oral and written communications ​​that have systematic, rational, empirical characteristics as a description of the structure and rules of language. This present study argues that the meaning of a word in language can be known with the foundation of semantic science. The problems this present study focused on are the seven types of meaning and their descriptions in the book of Semantics by Geoffrey Leech: 1981. The research aims to classify and to identify seven types of meanings, and also to analyze Leech’s book and three article reviews of his theory. This present study uses a qualitative approach focusing on the words, phrases, and sentences regarding the theory. The result of this research confirmed that there are seven types of meaning based on Leech’s theory, namely conceptual, connotative, collocative, reflective, affective, social, and thematic. A novelty that this present study found is that the seven types of meaning have variations in their descriptions.